Epstein-Barr virus-encoded LMP-1, LMP-2A and LMP-2B proteins in cell cycle regulation / Yeo Kok Siong - Yeo, Kok Siong (2012)
Epstein-Barr virus (EBV) is a ubiquitous tumour-causing virus which infects more than 90% of world population asymptomatically. It is closely associated with nasopharyngeal carcinoma (NPC). LMP-1, -2A and -2B are three latent membrane proteins (LMPs) encoded by EBV which are frequently detected in NPC tumour. Recent studies suggest that these three proteins co-operate in the tumorigenesis of NPC but the mechanism is not clear. In this study, LMPs were cloned into pcDNA3.1 and transfected into HEK293T cell line to reveal their oncogenic mechanism via investigation on their involvement in the regulation of cell cycle and genes that are involved. The transcription of cell cycle arrest genes were examined via semi-quantitative reverse transcription-PCR and real time PCR. Cell cycle progression was examined via flow cytometry. LMPs were successfully cloned in pcDNA3.1 and expressed in HEK293T in single and co-expression manner. 14-3-3σ and Reprimo were upregulated in all LMP-1 expressing cells. Moreover, cell cycle arrest at G2/M progression was detected in all LMP-1 expressing cells. Therefore, we conclude that LMP-1 may induce cell cycle arrest at G2/M progression via upregulation of 14-3-3σ and Reprimo.